#MeToo and beyond : perspectives on a global movement - Alcalde, M. Cristina; Villa, Paula-Irene (University Press of Kentucky, 2022)
#NiUnaMenos #Aufschrei #LoSHA. Before #MeToo became the massive global movement we know today, these were the hashtags that represented mobilisations from Ukraine to Latin America that demanded accountability for the intersecting experiences of sexual violence and racism, xenophobia, and misogyny inflicted on women, transgender people, and girls. Lead by activists such as Tarana Burke, who coined the phrase 'me too,' the movement provided a call to action for survivors across the world to speak out about their experiences. In '#MeToo and Beyond,' M. Cristina Alcalde and Paula-Irene Villa bring together scholars and activists from various backgrounds to approach #MeToo from multiple spaces, positionalities, and areas of expertise, many from regions and contexts often overlooked and understudied in the mediascapes of the Global North.